Study on the Breeding of L-Valine Producing Mutants (Prototroph and Auxotroph) and Comparison of Their Properties - Huanmin, Liu; Xiangyang, Ge; Weiguo, Zhang (Asian Journal of Chemistry, 2011)
NVS-137 and JVK-427 were isolated from mutagenesis on strain ZQM-246.Strain NVS-137 is prototroph, while strain JVK-427 is auxotroph. The results indicates strain NVS-137 is superior to JVK-423 in the fermentation process. Addition of biotin had an effect on L-valine fermentation and dry weight of cells.